Določanje privzema imatiniba v levkocite kot napovedni dejavnik uspešnosti zdravljenja KML - Kralj, Eva (Zdravniški vestnik, 2012)
Background: Imatinib is the first target therapy for chronic myelogenous leukemia (CML). Response to imatinib treatment also depends on the uptake of the drug into the target cell by organic cation transporter 1 (OCT1). OCT1 activity determined by the uptake of 14C-imatinib (IUR) in isolated mononuclear cells (MNC) has already been linked with treatment response. It has been proposed that the OCT1 activity determination could provide a valuable tool for the prediction of treatment success in patients with CML. Methods: MNC and granulocytes (Gran) of a healthy volunteer were incubated with imatinib in the presence or absence of prazosin before and after Ficoll cell sorting. The cells were lysed with liquid nitrogen and extracted with organic solvents. The intracellular concentration (c i ) of imatinib wasdetermined by LC-MS/MS method. Results: We measured the highest IUR in Granisolated prior to incubation with imatinib. There the c i was 10-fold higher than in other cells. With prazosin, significantly lower imatinib c i were ob - served in MNC (1.49 Ž 0.11 vs. 17.8 Ž 1.6 mg/L) and Gran (96.2 Ž 2.2vs. 191.2 Ž 7.7 mg/L) incubated after cell sorting. We measured the highest absolute OCT1 activity in Gran (6.27 Ž 0.66 ng imatinib/200000 cells).Conclusions: We developed a procedure for the measurement of imatinib uptake into the white blood cells, which is not based on the use of radi - oactively labelled compounds. By means of this test, we also hope to determinethe correlation of OCT1 activity with treatment success in the population of Slovenian CML patients.
Keywords: imatinib; kronična mieloična levkemija; levkociti